STUDENTS’ PERCEPTIONS TOWARD EFL TEACHER’S TEACHING STYLE AND HOW IT AFFECTS LEARNING MOTIVATION : A CASE STUDY - Siti Fajriah Kurnia Putri; Kusrin Kusrin (IKIP Siliwangi, 2022)
A teacher’s teaching style is the way he/she conducts class instruction an the classroom environment, every teacher has their own belief, ideology, and teaching style. In the end, teaching style may affect learning motivation of the students in the classroom. This study aimed to investigate how the students perceive their EFL teacher's teaching style and how the style affects students' motivation in English learning. The study was a qualitative study, the type of qualitative study used was a case study. The data collected from questionnaire that distributed to 13 students of an islamic senior high school, the interview data from 5 sudents used to verify the data. The results indicated that the students’ EFL teacher used facilitator style, and the students’ perceived that it was good. Most of the students said that the way their EFL teacher teaching affected their learning motivation. The researcher conclude that a teacher teaching style could motivate or demotivate students’ learning motivation. Through this study, the reseacher suggested to all EFL teachers in the future to pay more attention to their teaching styles, in order to boost their students motivation in learning and the learning objectives will be attained well. Keywords: Case Study, Learning Motivation, Students’ Perception, Teaching Style